(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: At seasonal tourist destinations like Shimla, rooms may remain vacant and unoccupied during lean peri ods. To add on, pandemic has already shut many small lodging facilities. Objective: The aim of this study is to improve our understanding of how homestay activities can contribute to revitalize sustainable tourism trends in Shimla, the study assumes particular importance in a period of economic crisis characterized by post covid trauma. Methodology: A survey was conducted in Shimla after first wave of corona virus from September 20 to December 20 as soon as the travel restrictions were uplifted. The travel and accommodation preferences of tourists were observed and found to be shifting towards less frequently visited places avoiding mass tourism. To highlight the role of homestays in reviving these tourism trends, three objectives were identified. Two separate questionnaires were developed to get the quantitative and qualitative data for this research. The data was tabulated and evaluated using SPSS tool. Results: The findings presented the analysed profile of the potential homestay operators as well as visitors seeking homestay tourism. It also reports the motivations, expectation and experience of the tourists regarding various aspects of homestay. Conclusion: Homestays can act as potential vital tool in reviving tourism.